Examining large-scale solar (LSS) photovoltaic (PV) operating utilities by using environmental impact screening (EIS) - Siti Isma Hani Ismail; Nur Syaza Syazwiena; Mohd Norman; Noorsuhada Md Nor; Zulfairul Zakaria; Siti Hafizan Hassan (Penerbit Universiti Kebangsaan Malaysia, 2023)
For Malaysia’s future energy needs, solar photovoltaic (PV) technology and farming is becoming a more cost- effective option and technology in achieving Malaysia’s goal of having 31% renewable energy in its power mix by year 2025. Malaysia’s global climate commitment is to reduce its economy-wide carbon intensity (as a percentage of GDP) by 45% by 2030 compared to 2005 levels. Realizing the government’s vision is critical to assisting the country in meeting its Nationally Determined Contributions (NDC) targets (SEDA, 2022). Hence, this paper highlights the evaluation of an existing solar farm located at Seberang Perai Pulau Pinang, Malaysia as a case study to examine the potential environmental impact arising from of large-scale solar (LSS) PV development utilising the Analytic Hierarchy Process (AHP) under the Multi-Criteria Decision Making (MCDM) technique.